Vegetative-vascular dystonia: diagnosis and treatment with the inclusion of modern methods of physiotherapy - N. I. Samosyuk; I. Z. Samosyuk; S. N. Fedorov; E. N. Chuhraeva; W. Zukow (Kazimierz Wielki University, 2015)
Samosyuk N. I., Samosyuk I. Z., Fedorov S. N., Chuhraeva E. N., Zukow W. Вегетативно-сосудистая дистония: диагностика и лечение с включением современных методов физиотерапии = Vegetative-vascular dystonia: diagnosis and treatment with the inclusion of modern methods of physiotherapy. Journal of Education, Health and Sport. 2015;5(7):117-152. ISSN 2391-8306. DOI 10.5281/zenodo.19327 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A117-152 https://pbn.nauka.gov.pl/works/578820 http://dx.doi.org/10.5281/zenodo.19327 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015.   Вегетативно-сосудистая дистония: диагностика и лечение с включением современных методов физиотерапии Vegetative-vascular dystonia: diagnosis and treatment with the inclusion of modern methods of physiotherapy   Samosyuk N. I.1, Samosyuk I. Z.1, Fedorov S. N.1, Chuhraeva E. N.1, Zukow W.2 Самосюк Н. И.1, Самосюк И. З.1, Федоров С. Н., Чухраева Е. Н.1, Жуков В. А.2   1National Medical Academy of post-graduate education named after P. L. Shupyk, Kiev, Ukraine 2Kazimierz Wielki University, Bydgoszcz, Poland 1Национальная медицинская академия последипломного образования имени П. Л. Шупика, Киев, Украина 2Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska   Резюме   В статье рассматриваются вопросы нейроциркуляторной дистонии и вегетативно-сосудистой дистонии, нозологическая принадлежность которых широко дискутируется в литературе. Авторы показывают в данной работе формирование клинического представления от «ВСД» и «НЦД», приводят классификацию, особенности их клинического течения и методики современной физиотерапии. Статья может представлять интерес широкому кругу врачей: неврологам, терапевтам, семейным врачам, врачам общей практики, студентам старших курсов медицинских ВУЗов и др.   Ключевые слова: вегетативно-сосудистая дистония, вегето-сосудистая дистония, диагностика, лечение, физиотерапия.   Abstract   The article discusses using neuro-circulator dystonia and vegetative-vascular dystonia, nosologic belonging which is widely discussed in the literature. In this paper, the authors show the formation of the clinical presentation of "VCD" and "NCD", lead classification, peculiarities of their clinical evolution and modern methods of physiotherapy. The article may be of interest to a wide range of doctors: neurologists, general practitioners, family doctors, physicians, undergraduate students of medical universities, etc.   Key words: vegetative-vascular dystonia, vegeto-vascular dystonia, diagnosis, treatment, physiotherapy.     Содержание   Вступление Соматоформные расстройства Лечение расстройств, связанных с психогенным дистрессом Соматизированные депрессии Условия, в которых должна проводиться медицинская помощь больным с ВСД Формирование клинического представления «ВСД» и некоторые возможные причины ее развития, варианты течения Классификация Клиника Диагностика Лечение. Общие рекомендации Современные методы физиотерапии в лечении НЦД и ВСД